Discount models in intertemporal choice: An empirical analysis - Isabel María Parra Oller; Salvador Cruz Rambaud; María del Carmen Valls Martínez (European Journal of Management and Business Economics (EJM&BE), 2021)
Purpose - The main purpose of this paper is to determine the discount function which better fits the individuals' preferences through the empirical analysis of the different functions used in the field of intertemporal choice. Design/methodology/approach - After an in-depth revision of the existing literature and unlike most studies which only focus on exponential and hyperbolic discounting, this manuscript compares the adjustment of data to six different discount functions. To do this, the analysis is based on the usual statistical methods, and the non-linear least squares regression, through the algorithm of Gauss-Newton, in order to estimate the models' parameters; finally, the AICc method is used to compare the significance of the six proposed models. Findings - This paper shows that the so-called q-exponential function deformed by the amount is the model which better explains the individuals' preferences on both delayed gains and losses. To the extent of the authors' knowledge, this is the first time that a function different from the general hyperbola fits better to the individuals' preferences. Originality/value - This paper contributes to the search of an alternative model able to explain the individual behavior in a more realistic way.
Keywords: 650; Discount function; Discounted utility model; Empirical analysis; Intertemporal choice; Preferences